THE INFLUENCE OF PROBLEM BASED LEARNING (PBL) LEARNING MODEL BASED ON INFOGRAPHIC MEDIA ON THE ABILITY TO WRITE BIOGRAPHICAL TEXTS IN CLASS X OF SMAN 6 KARAWANG: PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS MEDIA INFOGRAFIS TERHADAP KEMAMPUAN MENULIS TEKS BIOGRAFI KELAS X SMAN 6 KARAWANG - Bela Pathana; Sutri; Dewi Suprihatin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The problem in this research is whether there is an influence of the problem learning model based learning on the ability to write biographical texts of class X SMAN 6 students Karawang. This research aims to find out whether there is an influence of the model problem based learning on students' ability to write biographical texts class X at SMAN 6 Karawang. This type of research is experimental research with using the Nonequivalent Control Group Design research design, which is one of the experimental types. The population in this study were class X SMAN students 6 Karawang with 252 students. The sample in this study were students in class X-1 and X-2 consisted of 72 students using purposive sampling. Results This research shows that the research data collected. Testing hypothesis using two means test analysis. Based on the calculation results, class experiment and control obtained Sig values. (2-tailed) posttest data is 0.001, then Ho is accepted because of the Sig value. (2-tailed) < 0.05. Therefore, the learning model Problem Based Learning (PBL) based on infographic media can be influenced and used in the ability to write biographical texts in class X students at SMAN 6 Karawang.